Growth, development and nutritional value of Amaranthus tricolor L. as affected by salinity and harvesting procedure - Ribeiro, J. E. M. M. (Jeronimo Ernesto Meneses Machado) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2004.